2017
DOI: 10.1049/iet-nbt.2016.0204
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial, anti‐inflammatory and antioxidant effects of acetyl‐11‐α‐keto‐β‐boswellic acid mediated silver nanoparticles in experimental murine mastitis

Abstract: Mastitis is an important economic disease causing production losses in dairy industry. Antibiotics are becoming ineffective in controlling mastitis due to the emergence of resistant strains requiring the development of novel therapeutic agents. In this study, the authors present the phytochemical synthesis of silver nanoparticles (AgNPs) with acetyl-11-α-keto-βboswellic acid and evaluation of their activity in Staphylococcus aureus induced murine mastitis. Boswellic acid mediated AgNP (BANS) were oval, polydis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…8,9 AKBA, a pentacyclic terpenoid, is the active component of frankincense and has been exploited for various medicinal applications, such as antibacterial, anti-inflammatory, analgesic, anti-oxidant. 10,11 Recently, AKBA was also found to exhibit antitumor effects in human cell lines established from prostate cancer, breast cancer and glioblastoma. [12][13][14] Csuk et al demonstrated that boswellic acid and its derivatives induce apoptosis in breast and cervical cancers cells.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 AKBA, a pentacyclic terpenoid, is the active component of frankincense and has been exploited for various medicinal applications, such as antibacterial, anti-inflammatory, analgesic, anti-oxidant. 10,11 Recently, AKBA was also found to exhibit antitumor effects in human cell lines established from prostate cancer, breast cancer and glioblastoma. [12][13][14] Csuk et al demonstrated that boswellic acid and its derivatives induce apoptosis in breast and cervical cancers cells.…”
Section: Introductionmentioning
confidence: 99%
“… Acetyl-11- α -keto- β -boswellic acid -mediated silver nanoparticles showed superior antibacterial, anti-inflammatory, and antioxidant properties than cefepime in mastitis-induced mammary glands in mice 55 . …”
Section: Resultsmentioning
confidence: 94%
“…S. aureus is one of the leading causes of mastitis, resulting in an annual economic loss of $2 billion globally. S. aureus is also responsible for the emergence of resistant organisms and antibiotic residues in dairy products 55 . Acetyl-11- α -keto- β -boswellic acid-mediated silver nanoparticles (BANS, 0.12 mg · kg −1 , intramammary and intraperitoneal) were reported to exert superior antibacterial (36%), anti-inflammatory (95%), and antioxidant effects compared with the antibiotic cefepime (1 mg · kg −1 , intraperitoneal) in S. aureus -induced murine mastitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations